Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (My University, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 degrees S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica's ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Keywords: Antarctic ice sheet; Elevation (ballistics); Outcrop; Iceberg